Oocyst Simultaneous Infection to Increase Broiler Immunity from Coccidiosis - Setyawati, SJA; Yuwono, E (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
Coccidiosis is one of parasitic disease caused by Eimeria which is frequently occurs in broiler chick. The disease produces enteritis diarrhea that affects viability and growth. Stimulating its immune could be done by repeated light oocyst infection. This research purposed to study infection level and frequency of Eimeria tenella on coccidiosis immunity and broiler performance. Factorial 2 X 3 was applied with infection level as the first factor: 10.000 oocyst (B1); and 20.000 oocysts (B2). The second factor was infection frequency: once (A1); twice (A2); and three times (A3). The first infection was at 10 days old and the next was 7 days later. Each experiment unit had 8 broilers, and it was replicated 4 times. On 30 days old, challenge test was conducted by infection using 25.000 oocysts per broiler. Parameter observed were oocyst elimination, caecum treatment score and clinical symptom post inoculation and post test, weekly body weight, final weight, and feed conversion. Data were analyzed using variance analysis and Honestly Significant Difference (HSD) test. Weekly body weight and clinical symptom were described. The result indicated that broiler infected by Eimeria tenella oocyst simultaneously with 20.000 oocysts caused immunization. The number of oocyst did not have significant effect on the performance. (Animal Production 8(1): 72-77 (2006) Key Words : Eimeria tenella, enteritis diareal, performance, immunization.